PERIARTICULAR REGIONAL ANALGESIA REDUCES PAIN AND HOSPITAL STAY AFTER TOTAL KNEE ARTHROPLASTY: A PROSPECTIVE, RANDOMIZED, AND DOUBLE-BLINDED CONTROLLED TRIAL - DAS, PULIN BIHARI; SINGH, ANAND KUMAR; CHATTERJEE, ARINDAM; SINGH, ANURAG (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: There are multiple post-operative pain protocols for patients who undergo total knee arthroplasty (TKA). Post-operative analgesia with opioids or epidural analgesia has its side effect. We compared the duration of hospital stay, pain score, and range of motion of a control group who had no local infiltration with a group who had local infiltration analgesia following TKA. Methods: Randomization was done in 60 patients who underwent TKA in two groups, one who did not receive and the other who received a multimodal cocktail periarticular injection containing 30 ml of 0.5% bupivacaine, 1 ml of 30 mg ketorolac, 1 ml of 1 in 1000 adrenaline, 2 ml of 80 mg gentamycin, 5 ml of 750 mg cefuroxime, and rest 0.9% of normal saline. Visual analog score (VAS) for pain at rest was recorded and assessed preoperatively and postoperatively at 2, 6, 12, 24, 36 h, 2, 3, and 7 days and during an activity at 24 h, 36 h, 2, 3, and 7 days. Results: The patient who had received the local injection used very few analgesics over the first 24 h of surgery. Moreover, patients, where local infiltration was used, showed lower VAS for pain (at rest and during activity). They also showed higher VAS for patients’ satisfaction. Conclusion: Due to the reduced post-operative pain with periarticular injection analgesia, it was observed that the pain and duration of hospital stay were significantly reduced.